Українські релігійні стереотипи в контексті формування сучасної релігійної ідентичності - Клімук, І. М.; Klimuk, І. М. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано проблему взаємозв’язку релігійних стереотипів та ідентичності. Розкрито сприйняття релігійних стереотипів особистістю і їх вплив на формування індивідуальної та колективної релігійної іден-тичності сучасного українця. During the socio-cultural and economical transformation of Ukrainian society that affect the identification process, the relevance of the formation of modern religious identity is increased. Religious identity is not a fixed constant, which is given to a person at birth, it is constructed by the individual depending on the individual and social conditions. This article analyzes the ukrainian religious stereotypes as one of the most important factors that influence the formation and transformation of the religious identity of Ukrainians. The paper describes the peculiarities of appearance of religious stereotypes and their functioning on the territory of Ukraine. The main characteristics of ukrainian religious stereotypes are highlighted. The author shows the importance of the role of religious stereotypes in formation of personal and group religious identity. It is noted, that the changes of religious stereotypes produce transformation of religious identity.
Ukrainian Religious Stereotypes in the Context of the Formation of Modern Religious Identity
Keywords: стереотип; stereotype; релігійний стереотип; religious stereotype; індивідуальна релігійна ідентичність; personal religious identity; конфесійна ідентичність; confessional identity